2014
DOI: 10.3389/fnbeh.2014.00123
|View full text |Cite
|
Sign up to set email alerts
|

Diminished N1 Auditory Evoked Potentials to Oddball Stimuli in Misophonia Patients

Abstract: Misophonia (hatred of sound) is a newly defined psychiatric condition in which ordinary human sounds, such as breathing and eating, trigger impulsive aggression. In the current study, we investigated if a dysfunction in the brain’s early auditory processing system could be present in misophonia. We screened 20 patients with misophonia with the diagnostic criteria for misophonia, and 14 matched healthy controls without misophonia, and investigated any potential deficits in auditory processing of misophonia pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 29 publications
5
62
1
2
Order By: Relevance
“…This suggested the encoding deficits in auditory processing information of hearing impaired subjects. Our finding agreed with that of the previous studies where the low-level of N1 auditory response was found in subjects with misophonia and aphasia (Becker & Reinvang 2013;Schröder et al 2014). These similarities suggested that the center auditory process of sensorineural of the subject might interfere with some speech perception disorder.…”
Section: Effects Of the Features Of Speech Articulation On The Amplitsupporting
confidence: 83%
See 3 more Smart Citations
“…This suggested the encoding deficits in auditory processing information of hearing impaired subjects. Our finding agreed with that of the previous studies where the low-level of N1 auditory response was found in subjects with misophonia and aphasia (Becker & Reinvang 2013;Schröder et al 2014). These similarities suggested that the center auditory process of sensorineural of the subject might interfere with some speech perception disorder.…”
Section: Effects Of the Features Of Speech Articulation On The Amplitsupporting
confidence: 83%
“…The result of P1 component reported here fostering similarity with the previous finding where the average amplitude elicited from the SNHL subject was higher than the control group for both stimuli (Schröder et al 2014). The previous study emphasized the difficulty to assess accurately the P1 component due to the interaction with C1 waves from a visual event-related potential (VERP) component which created a major overlapping mechanism with the P1 CAEP component (Luck 2005).…”
Section: Effects Of the Features Of Speech Articulation On The Amplitsupporting
confidence: 75%
See 2 more Smart Citations
“…The reported disproportional aversive experience has been validated by finding an increased autonomic response (as measured with GSR 1 ) to trigger sounds, but not to corresponding visual stimuli, in misophonic participants compared with nonmisophonic participants (Edelstein et al, 2013). Furthermore, the reported sensory sensitivity has been corroborated with an altered early physiological signal (auditory N100) measured in an oddball paradigm with electroencephalogram (Schröder et al, 2014).…”
Section: Introductionmentioning
confidence: 78%